Colon Capsule Endoscopy: Review and Perspectives - David Friedel; Rani Modayil; Stavros Stavropoulos (Gastroenterology Research and Practice)
Colon capsule endoscopy utilizing PillCam COLON 2 capsule allows for visualization potentially of the entire colon and is currently approved for patients who cannot withstand the rigors of traditional optical colonoscopy (OC) and associated sedation as well as those that had an OC that was incomplete for technical reasons other than a poor preparation. We will then describe the prior experience and current status of colon capsule endoscopy.